Letter from ECCOMAS President - Papadrakakis, Manolis (Computer Assisted Methods in Engineering and Science, 2012)
The year 2012 marks the 20th anniversary of the European Community on Applied Sciences and Engineering (ECCOMAS) and coincides with the VIth ECCOMAS Congress to be held in Vienna, Austria September 10–14, 2012, as well as with a number of initiatives taken by members of ECCOMAS. One of these initiatives is the launching of the present journal “Computer Assisted Methods in Engineering and Sciences” (CAMES). This journal is a continuation of the journal “Computer Assisted Mechanics and Engineering Sciences” published by the Polish Academy of Sciences, now to be published under the auspices of ECCOMAS with a broader scope and a renewed Editorial Board. The scope of CAMES will cover all subjects traditionally addressed by ECCOMAS in the broader field of numerical methods and computer simulation in engineering and applied sciences.